DESAIN MANAJEMEN BISNIS DESA WISATA DI DESA BANJARWARU KECAMATAN LUMAJANG KABUPATEN LUMAJANG - Aris Sunandes; Palupi Puspitorini; Yuhanin Zamrodah; Rumanintya L Putri (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2022)
The research aims to identify business potential, develop and design tourism village business management in Banjarwaru Tourism Village, Lumajang District, Lumajang Regency. This research is a qualitative type with a case study approach. Primary data sources were obtained from interviews and focus group discussions and direct observation as a form of triangulation validity. Data analysis techniques through the stages of data reduction, data analysis, verification and conclusion. The results of mapping the potential of Banjarwaru village and the focus group discussions that have been carried out show that there is potential for village natural resources that are developed in the short term and in the long term including preneur sport-based tourism which is supported by its facilities, namely Mini soccer, white water rafting, culinary tourism, homestay. The development of a tourist village includes four aspects that can be developed and support each other, namely, aspects of attractiveness, accessibility, facilities and institutions. The design of tourism village business management in Banjarwaru Tourism Village, Lumajang District, Lumajang Regency, the management is included in the BUMDES section as a village-owned business based on community services but has the ultimate goal of achieving profit, it should be managed professionally like a business in general, even though the ownership and character of the The organization is based on community service. Professional management includes marketing management, financial management, human resource management and production management.